Enhancing Renal Autophagy via Yangshen Paidu Decoction: AMPK/mTOR Pathway Modulation in Chronic Renal Failure Management - Tang, Hao; Tao, Qi; Li, Yifan; Bai, Xiaohui; Lv, Dan; Wang, Fang; Pan, Ronghua; Zhao, Yanmei (Letters in Drug Design & Discovery, 2024)
ObjectiveChronic Renal Failure (CRF) refers to the gradual decline in renal function caused by various chronic kidney diseases, eventually leading to end-stage renal failure. Yangshen Paidu Decoction (YPD) is a Traditional Chinese medicine (TCM) formula utilized in CRF treatment. This work has analyzed the effects of YPD on CRF and the specific mechanism.MethodsNetwork pharmacology was performed to screen effective components and targets of YPD, from which key targets and signaling pathways contributing the most to the treatment effects on CRF were determined. Subsequently, we validated the therapeutic role of YPD and the underlying pathological mechanisms using the 5/6-nephrectomy rat model.ResultsNetwork pharmacology analysis showed the mTOR pathway to be a pivotal mechanism underlying the effectiveness of YPD in CRF treatment. YPD significantly suppressed urine protein levels, blood urea nitrogen, and serum creatinine in 5/6 nephrectomized rats. Furthermore, YPD remarkably improved renal pathological injuries. Western blot analysis revealed that YPD enhanced autophagy and upregulated the expression of nephrin, podocin, beclin1, p-AMPK/AMPK, and p-ULK1/ULK1, and attenuated the ratios of p-mTOR/mTOR to its downstream protein phosphorylated eIF4E-binding protein (p-4EBP1). However, these effects were notably reversed by the AMPK inhibitor compound C.ConclusionOur findings have demonstrated YPD to suppress the mTOR pathway and stimulate autophagy by modulating AMPK pathways, thereby mitigating podocyte injury and enhancing renal function. Our study has confirmed autophagy and the AMPK/mTOR pathway as potential targets for YPD in CRF treatment.
Keywords: Chronic renal failure